ANALISIS PENGARUH RETURN ON ASSETS, NET PROFIT MARGIN RETURN ON EQUITY, DEBT TO EQUITY RATIO, DAN DEBT TO ASSET RATIO UNTUK MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - MUHAMMAD ABDUL MUIS (JMB : Jurnal Manajemen dan Bisnis, 2020)
ABSTRACT : This research aims to analyze the ability of Net Profit Margin, Return On Assets, Return on Equity, Debt to Equity Ratio and Debt to Asset Ratio on Financial Distress in Sector Manufacture Companies listed on Indonesia Stock Exchange period 2014-2017.The research methodology used quantitative method with panel data and secondary data obtained from financial statement on Indonesia Stock Exchange. Mechanical sampling used purposive sampling that consist of 44 sector manufacture companies listed on Indonesia Stock Exchange. The data analysis technique used is logistic binary regression.The result of this study indicate that Return On Assets and Return on Equity have significant influence on Financial Distress, however Net Profit Margin, Debt to Equity Ratio and Debt to Asset Ratio has not influence on Financial Distress. Meanwhile, Net Profit Margin, Return On Assets, Return on Equity, Debt to Equity Ratio and Debt to Asset Ratio simultaneously have significant influence on Financial Distress. And the result of this study indicate that value of McFadden  is 0.909291 or 90.92% which means that the dependent variable of financial distress can be explained by the independent variables NPM, ROA, ROE, DER, and DAR of 47,57% while the remaining 9.08% were other factors beyond the models that explain the dependent variable. Keywords     : Financial Distress, NPM, ROA, ROE, DER, DAR, McFadden